Cell specific photoswitchable agonist for reversible control of endogenous dopamine receptors - Prashant Donthamsetti (Nature Portfolio, 2021)
In this study, the authors develop a photo-pharmacological strategy using a Membrane anchored Photoswitchable orthogonal remotely tethered agonist for the Dopamine receptor (MP-D) to selectively and reversibly modulate the D1R receptor subtype.